2022
DOI: 10.3389/fcell.2022.946484
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferase KMT2D contributes to the protection of myocardial ischemic injury

Abstract: Histone H3 lysine 4 (H3K4) methyltransferase 2D (KMT2D) plays an important role in cell development in early life. However, the function of KMT2D in adult cells such as cardiomyocytes or neurons has not been reported. In this study, cardiomyocyte-specific KMT2D knockout (KMT2D-cKO) and control (KMT2D-Ctl) mice were exposed to sham or myocardial ischemia (MI) surgery. Depletion of KMT2D aggravated the ischemic area, led to the increased mortality (26.5% in KMT2D-cKO vs 12.5% in KMT2D-Ctl) of the mice, and weake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Suppressed vascular density of Kmt2d cardiomyocyte-specific knockout mice after MI may be attributed to the inhibition of the paracrine effects of cardiomyocytes on ECs mediated by KMT2D deficiency. To this end, Kmt2d gene was deleted in H9c2 cardiomyocytes using the CRISPR/Cas9 gene-editing knockout system as previously reported [ 14 ], after which the CM was collected from the cardiomyocytes cultured for 24 h under normoxia or hypoxia (1% O 2 ) and added into EC culture. After determining that KMT2D protein was significantly knocked down in H9c2 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Suppressed vascular density of Kmt2d cardiomyocyte-specific knockout mice after MI may be attributed to the inhibition of the paracrine effects of cardiomyocytes on ECs mediated by KMT2D deficiency. To this end, Kmt2d gene was deleted in H9c2 cardiomyocytes using the CRISPR/Cas9 gene-editing knockout system as previously reported [ 14 ], after which the CM was collected from the cardiomyocytes cultured for 24 h under normoxia or hypoxia (1% O 2 ) and added into EC culture. After determining that KMT2D protein was significantly knocked down in H9c2 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of KMT2D protein significantly reduces the transcription activity of target genes [ 35 ]. Our previous studies demonstrated that cardiomyocyte-specific KMT2D knockout mice exhibited larger infarct size after myocardial infarction surgery with reduced expression of functional genes [ 14 ]. In the current study, we detected impaired angiogenesis and reduced level of H3K4me1 in the Vegf-a promoter region during MI in the cardiomyocyte-specific Kmt2d knockout mice and KMT2D silenced H9c2 cardiomyocyte respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations